Senescence as an Amyloid Cascade: The Amyloid Senescence Hypothesis - Walton, Chaska C.; Begelman, David; Nguyen, Wynnie; Andersen, Julie K. (Frontiers in Cellular Neuroscience, 2020)
Abstract: Due to their postmitotic status, the potential for neurons to undergo senescence has historically received little attention. This lack of attention has extended to some non-postmitotic cells as well. Recently, the study of senescence within the central nervous system (CNS) has begun to emerge as a new etiological framework for neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The presence of senescent cells is known to be deleterious to non-senescent neighboring cells via development of a senescence-associated secretory phenotype (SASP) which includes the release of inflammatory, oxidative, mitogenic, and matrix-degrading factors. Senescence and the SASP have recently been hailed as an alternative to the amyloid cascade hypothesis and the selective killing of senescence cells by senolytic drugs as a substitute for amyloid beta (Aß) targeting antibodies. Here we call for caution in rejecting the amyloid cascade hypothesis and to the dismissal of Aß antibody intervention at least in early disease stages, as Aß oligomers (AßO) and cellular senescence may be inextricably linked. We will review literature that portrays AßO as a stressor capable of inducing senescence. We will discuss research on the potential role of secondary senescence, a process by which senescent cells induce senescence in neighboring cells, in disease progression. Once this seed of senescent cells is present, the elimination of senescence-inducing stressors like Aß would likely be ineffective in abrogating the spread of senescence. This has potential implications for when and why AßO clearance may or may not be effective as a therapeutic for AD. The selective killing of senescent cells by the immune system via immune surveillance naturally curtails the SASP and secondary senescence outside the CNS. Immune privilege restricts the access of peripheral immune cells to the brain parenchyma, making the brain a safe harbor for the spread of senescence and the SASP. However, an increasingly leaky blood brain barrier (BBB) compromises immune privilege in aging AD patients, potentially enabling immune infiltration that could have detrimental consequences in later AD stages. Rather than an alternative etiology, senescence itself may constitute an essential component of the cascade in the amyloid cascade hypothesis.